2016
DOI: 10.1021/acs.chemrestox.6b00169
|View full text |Cite
|
Sign up to set email alerts
|

Human Microdosing with Carcinogenic Polycyclic Aromatic Hydrocarbons: In Vivo Pharmacokinetics of Dibenzo[def,p]chrysene and Metabolites by UPLC Accelerator Mass Spectrometry

Abstract: Metabolism is a key health risk factor for exposures to pro-carcinogenic polycyclic aromatic hydrocarbons (PAHs) such as dibenzo[def,p]chrysene (DBC), an IARC classified 2A probable human carcinogen. Human exposure to PAHs occurs primarily from the diet in non-smokers. However, little data is available on the metabolism and pharmacokinetics in humans of high molecular weight PAHs (≥4 aromatic rings), including DBC. We previously determined the pharmacokinetics of DBC in human volunteers orally administered a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…DBC, a six-membered PAH with both a bay-and fjord-region, is a potent carcinogen in preclinical rodent models (probable compared to BaP. In the study with [ 14 C]-DBC, the major plasma metabolite observed was tentatively identified as DBC-11,12-DHD yet we found no evidence of covalent DNA adduction in PBMCs (Madeen et al, 2016). In this study with [ 14 C]-BaP, although extensive metabolism was evident, little or no covalent DNA adduction was observed 48-72 hours after dosing.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…DBC, a six-membered PAH with both a bay-and fjord-region, is a potent carcinogen in preclinical rodent models (probable compared to BaP. In the study with [ 14 C]-DBC, the major plasma metabolite observed was tentatively identified as DBC-11,12-DHD yet we found no evidence of covalent DNA adduction in PBMCs (Madeen et al, 2016). In this study with [ 14 C]-BaP, although extensive metabolism was evident, little or no covalent DNA adduction was observed 48-72 hours after dosing.…”
Section: Discussionmentioning
confidence: 59%
“…The [ 14 C]-BaP metabolite profile for volunteers BaP002 and BaP009 was assessed over the 72 hour time course utilizing the moving wire UPLC-AMS system developed by the Biomedical Research group at LLNL (Thomas et al, 2011;Ognibene et al, 2015;Madeen et al, 2016). Unlike the case with [ 14 C]-DBC (Madeen et al, 2016), [ 14 C]-BaP (21.86 min) was a minor component even at the earliest time points post-dosing (Fig. 3).…”
Section: Time Course Of [ 14 C]-bap Metabolites In Plasma Of Two Volumentioning
confidence: 99%
“…EPA, 2017). Accelerator mass spectrometry (AMS), with its high sensitivity (low attomole) (Forsgard et al, 2010) allows for study of the pharmacokinetics of human carcinogens at doses that represent a de minimus risk to subjects (Cupid et al, 2004; Garner et al, 1999; Jubert et al, 2009; Lightfoot et al, 2000; Madeen et al, 2015; 2016; Malfatti et al, 2016; Turteltaub et al, 1997). Previously, our laboratory determined the pharmacokinetics of aflatoxin B 1 (AFB 1 ) (Jubert et al, 2009), and dibenzo[ def,p ]chrysene (DBC) (Madeen et al, 2015; 2016) in humans at doses below the LDAL and [ 14 C] amounts (5 nCi) that are orders of magnitude lower than previously used in diagnostic procedures (Atherton and Spiller, 1994) or clinical trials (Ottaviani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The moving wire interface was used to measure human plasma and urine metabolism profiles following environmentally relevant exposures to the polycyclic aromatic hydrocarbons, dibenzo[def,p]chrysene (DBC) (Figure 1) [18] and benzo[a]pyrene [19]. Due to their toxicity, doses to healthy human volunteers were required to be kept as low as possible to minimize risk and the metabolite levels recorded following HPLC separation were so low that they could only have been measured as a CO 2 gas.…”
Section: Technologymentioning
confidence: 99%